Piperine enhances carbohydrate/fat metabolism in skeletal muscle during acute exercise in mice - Jisu Kim; Kang-Pa Lee; Dae-Won Lee; Kiwon Lim (Nutrition & Metabolism, 2017)
Abstract Background Exercise promotes energy metabolism (e.g., metabolism of glucose and lipids) in skeletal muscles; however, reactive oxygen species are also generated during exercise. Various spices have been reported to have beneficial effects in sports medicine. Here, we investigated the effects of piperine, an active compound in black pepper, to determine its effects on metabolism during acute endurance exercise. Methods ICR mice (n = 18) were divided into three groups: nonexercise (CON), exercise (EX), and exercise with piperine (5 mg/kg) treatment (EP). Mice were subjected to enforced exercise on a treadmill at a speed of 22 m/min for 1 h. To evaluate the inflammatory responses following exercise, fluorescence-activated cell sorting analysis was performed to monitor changes in CD4+ cells within the peripheral blood mononuclear cells (PBMCs) of mice. The expression levels of metabolic pathway components and redox-related factors were evaluated in the soleus muscle by reverse transcription polymerase chain reaction and western blotting. Results There were no changes in the differentiation of immune cells in PBMCs in both the EX and EP groups compared with that in the CON group. Mice in the EX group exhibited a significant increase in the expression of metabolic pathway components and redox signal-related components compared with mice in the CON group. Moreover, mice in the EP group showed greater metabolic (GLUT4, MCT1, FAT/CD36, CPT1, CS) changes than mice in the EX group, and changes in the expression of redox signal components were lower in the EP group than those in the EX group. Conclusion Our findings demonstrate that piperine promoted beneficial metabolism during exercise by regulating carbohydrate/fat metabolism and redox signals. Therefore, piperine may be a candidate supplement for improvement of exercise ability.